POLITICAL ENTITIES OF LEGAL CULTURE IN CENTRAL ASIA - Absattarov Galymzhan Raushanbekovich (Academic Journal of Physical and Chemical Sciences, 2020)
With the help of specific materials, the article deals with the issues of political subjects of legal culture in Central Asia, which have not yet been studied in political science. The paper examines in more detail the various political subjects of legal culture - state, government and its bodies, political parties, and social and political movements in Central Asia. All political actors of the Central Asian countries participate in the formation and implementation of the state’s policy of legal culture. The article notes that Parliament, the President, the Government as a whole and the head of the Government separately, the Central Bank, the Ministry of Justice, the Ministry of Foreign Affairs, other ministries, state committees and commissions of Central Asian countries can act as political subjects of legal culture on behalf of the state. Political subjects of legal culture in Central Asia influence the creation of civil society and protect human rights and freedoms, honor and dignity. At the same time, the article focuses on discussing issues.